Wavelength selective photocontrol of hybrid azobenzene-spiropyran photoswitches with overlapping chromophores - Saßmannshausen, Torben; Kunz, Anne; Oberhof, Nils; Schneider, Friederike; Slavov, Chavdar; Dreuw, Andreas; Wachtveitl, Josef; Wegner, Hermann A. (Angewandte Chemie. International edition, 2024)
Compounds with multiple photoswitching units are appealing for complex photochemical control of molecular materials and nanostructures. Herein, we synthesized novel meta- and para- connected (related to the nitrogen of the indoline) azobenzene-spiropyran dyads, in which the central benzene unit is shared by both switches. We investigated their photochemistry using static and time-resolved transient absorption spectroscopy as well as quantum chemical calculations. In the meta-compound, the individual components are photochemically decoupled due to the meta-pattern. In the para-compound the spiro-connectivity leads to a bifunctional photoswitchable system with a red-shifted absorption. The azobenzene and the spiropyran can thus be addressed and switched independently by light of appropriate wavelength. Through the different connectivity patterns two different orthogonally photoswitchable systems have been obtained which are promising candidates for complex applications of light control.